The energy recovery from decanter cakes - Muhammad Lukman, Manshor (2009)
Harnessing energy from biomass had caught many researcher’s and scientists’ attention. Converting palm oil mill waste, decanter cakes into solid fuels is objective of this study especially to extract its potentiality to replace the existing boilers feed and to find the optimum condition that leads to the maximum energy recovery. The main steps involve in the process is pyrolysis at temperature ranges from 300°C to 600°C, the drying or heating process for 24 hours at temperature of 110°C and studying the combustion characteristics in terms of heating values and comparing it to that of the commercial solid fuels. The works carried in this research also involve the proximate analysis and semi-quantitative analysis that leads to the computation of HHV and it is compared with that from the Oxygen-bomb Calorimeter (OBC) .It also involve the combustion test of different diameter of DDCs and PDCs spheres to determine the optimum diameter. Based on the study, the decanter cakes is feasible to replace fiber and shell as boiler’s feed that promotes more than sufficient heat to dry the 70kg/ton of decanter cake in-plant and hence generates electricity with and excess steam around 289.075 kg/hr. In fact, the calculation revealed that decanter cakes are feasible to be used as a new boilers fuel when using a steam system from boiler. The fittings generated from the combination of the SEM & EDX data, TGA data and OBC data can be used to estimate the calorific values (J/g) of the solid fuels with percentage error of 0.01 % and 0.45 %. From the study, it can be concluded that the pyrolysis process of DDC did not increase the fixed carbon value and hence lowering the HHV of the solid fuels as the temperature of pyrolysis process increase. The dried decanter cakes at 110°C at 5 cm in diameter gives better solid fuels characteristics in terms of the heat value and flame characteristics compared to E-Ignite charcoal briquettes and charcoal briquettes derived from coconut shell.